Method for laser-induced in-situ preparation of boron-nitrogen co-doped hollow carbon nanocage
Through the laser-induced in situ preparation method, combining the mixing of boric acid nanoparticles and polyimide precursors and laser direct writing technology, the problems of high temperature, harsh conditions and use of harmful chemical reagents for the preparation of hollow carbon nanosphere cages were solved, and the efficient and environmentally friendly preparation of boron-nitrogen co-doped hollow carbon nanosphere cages were achieved, with excellent structural characteristics and wide application potential.
Patent Information
- Application Number
- CN202510049696.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-01-10
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
AI Technical Summary
The existing hard template method for preparing hollow carbon nanosphere cages has problems such as high operating temperature, strict reaction conditions, the difficulty of using harmful chemical reagents and doping regulation, which limits its efficient, environmentally friendly and controllable preparation.
Using laser-induced in situ preparation method, a boric acid nanoparticles were mixed with the polyimide precursor liquid polyamic acid to form an H3BO3/PI composite film, and a laser direct writing technology was used to carry out a carbonization reaction on the film, introducing boron and nitrogen elements, and then removing the template with hot water to prepare a boron and nitrogen co-doped hollow carbon nanosphere cage.
It has achieved efficient, environmentally friendly and controllable preparation of boron and nitrogen co-doped hollow carbon nanosphere cages, with excellent structural characteristics and wide application potential, and is suitable for large-scale production.
Smart Images

Figure CN119797340A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of hollow carbon nanomaterials, and in particular relates to a method for in-situ preparation of boron-nitrogen co-doped hollow carbon nano cages by laser induction. Background Art
[0002] As an innovative three-dimensional nanostructured material, hollow carbon nanocages have shown significant advantages in many fields with their unique three-dimensional structure and porous properties. These nanostructures are composed of curved carbon nanosheets, forming submicron gaps and subnano to nanometer channels, allowing efficient communication between the internal and external spaces. The high specific surface area and porosity of hollow carbon nanocages provide rich contact interfaces for material exchange. At the same time, the curved surface structure of this material helps to overcome the anisotropy problem existing in traditional carbon materials, reduces the risk of interlayer slip, and enhances the overall structural stability. In addition, hollow carbon nanocages are easy to dope with other elements or compounds, and their physical and chemical properties can be precisely controlled, which greatly broadens its scope of application.
[0003] Boron-nitrogen co-doped hollow carbon nanocage materials have shown a series of striking advantages. First, the synergistic doping strategy of boron and nitrogen cleverly adjusts the electronic structure of carbon materials, significantly improves their electrical conductivity and catalytic activity, and enhances their application potential in energy storage, catalytic reactions, etc. Secondly, its unique hollow structure design greatly increases the specific surface area and porosity of the material, which means higher energy storage density and more excellent cycle stability for energy storage devices such as batteries and supercapacitors. It is particularly worth mentioning that boron doping helps to improve the thermal stability of the material, while nitrogen doping can improve the hydrophilicity and catalytic activity of the material, thereby showing excellent performance in electrochemical properties, gas adsorption, and environmental purification. In summary, these characteristics give boron-nitrogen co-doped hollow carbon nanocages potential in advanced energy conversion and storage technologies, making it a promising new choice in scientific research and industrial applications.
[0004] In the process of preparing hollow carbon nano cages, the template method has attracted widespread attention due to its advantages such as precise structural control, simple operation and low cost. The template method is mainly divided into two types: hard template method and soft template method. The hard template method usually synthesizes hollow carbon nano cages with uniform morphology by coating a carbon precursor on a spherical template and carbonizing it, and then removing the template with acid or organic solvent. The soft template method forms a hollow structure by self-assembling a carbon precursor and a hydrophilic molecule to prepare hollow carbon nano cages. Although it avoids the use of corrosive chemicals in the hard template method, its disadvantages are poor structural stability, sensitivity to process conditions, limited self-assembly ability, and long reaction cycle. These factors limit its efficiency and reliability in large-scale production and application. Therefore, the hard template method has become a common method for preparing hollow carbon nano cages because of its simplicity and effectiveness.
[0005] However, the currently widely used hard template method for preparing hollow carbon nanoshells faces a series of challenges. First, this method often requires high operating temperatures and harsh reaction conditions, which undoubtedly increases the difficulty of process control. Secondly, the removal step of the hard template usually relies on harmful chemical reagents such as strong acids or strong bases, which not only pollutes the environment, but also leads to a huge waste of resources. Furthermore, the selection of doping source materials and the precise regulation of doping elements also face challenges, which directly leads to the uncertainty of the product structure and affects the performance and application effect of the material. Therefore, how to overcome these challenges and achieve efficient, environmentally friendly and controllable preparation of hollow carbon nanoshells by the hard template method is an important direction of current research. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention proposes an innovative laser-induced in-situ preparation method for boron-nitrogen co-doped hollow carbon nanocages, comprising the following steps: 1. Raw material preparation: Boric acid (H3BO3) nanoparticles are selected as the template of hollow carbon nanocages and the source of boron doping to ensure uniform particle size. At the same time, liquid polyamic acid (PAA), the precursor of polyimide (PI), is prepared as the source of carbon matrix and nitrogen doping.
[0007] 2. Mixing and dispersion: Disperse H3BO3 nanoparticles evenly in PAA solution, and ensure that H3BO3 nanoparticles are evenly distributed in PAA solution by ultrasonic and magnetic stirring to form a uniform H3BO3 / PAA mixed system.
[0008] 3. High-temperature imidization: The above-mentioned mixed system is evenly coated to prepare a H3BO3 / PAA film, and placed in a high-temperature environment for imidization reaction to convert PAA into PI. At the same time, the H3BO3 nanoparticles are wrapped in the PI matrix to form a H3BO3 / PI composite film.
[0009] 4. Laser direct writing: Laser direct writing technology is used to induce laser on the H3BO3 / PI composite film to induce carbonization reaction in the local area. At the same time, the boron element in H3BO3 and the nitrogen element in PI are introduced into the carbon structure under the action of laser, forming a boron-nitrogen co-doped carbon structure material in situ. Laser parameters (such as power, scanning speed, etc.) need to be adjusted according to the structure and performance of the target material.
[0010] 5. Template removal: Soak the film after the above treatment in hot deionized water for 60-120 minutes, and use the hot water to dissolve the boric acid nanoparticles and remove them from the carbon structure, leaving the boron-nitrogen co-doped hollow carbon nanocage structure.
[0011] 6. Drying treatment: Dry the sample after removing the template to completely remove residual moisture and obtain the final boron-nitrogen co-doped hollow carbon nanocage product.
[0012] Compared with the prior art, the beneficial effects of the present invention are: Innovative preparation process: The present invention adopts laser in-situ induction technology to efficiently synthesize boron-nitrogen co-doped carbon nanospheres in one step, and removes the template by water to obtain boron-nitrogen co-doped hollow carbon nanosphere cages. This process is not only simple to operate, environmentally friendly, but also cost-effective and extremely suitable for large-scale production.
[0013] Significant structural optimization: The prepared boron-nitrogen co-doped hollow carbon nanocages exhibit excellent structural properties, combining ultra-large specific surface area with outstanding wetting properties.
[0014] Broad application prospects: The boron-nitrogen co-doped hollow carbon nanocage shows broad application potential in advanced energy conversion and storage technologies such as fuel cell catalysts, supercapacitor electrodes, and lithium-ion battery electrodes, and can effectively improve the overall performance of related devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a transmission electron microscope (TEM) image of the boron-nitrogen co-doped hollow carbon nanocage prepared in Example 3; Figure 2 This is an X-ray photoelectron spectroscopy (XPS) graph of the boron and nitrogen co-doped hollow carbon nanocage prepared in Example 3. DETAILED DESCRIPTION
[0016] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0017] Embodiment: The accompanying drawings are intended to assist in a deeper understanding of the contents of the present invention. As an indispensable part of the specification, they are combined with the embodiments to illustrate the present invention together. However, they are not intended to set the boundaries of the present invention or limit its scope of application.
[0018] Figure 1 The hollow structure of carbon nanocages is clearly revealed, with diameters ranging from 20 to 80 nanometers.
[0019] Figure 2 (a) shows the full XPS spectrum of the boron-nitrogen co-doped hollow carbon nanocage. It can be clearly identified from the figure that in addition to the significant C 1s peak (located at 284.3 eV) and O 1s peak (located at 531.7 eV), there are also obvious B 1s peaks (192.4 eV) and N 1s peaks (400.0 eV). The appearance of these characteristic peaks strongly proves that boron and nitrogen elements have been successfully incorporated into the structure of the hollow carbon nanocage. Figure 2 (b) to Figure 2 (e) shows the high-resolution XPS spectra of C 1s, B 1s, N 1s and O 1s of the boron-nitrogen co-doped hollow carbon nanocages. Specifically, Figure 2 (b) reveals weaker peaks for the CB and COC=O bonds, with corresponding binding energies of 285.2 eV and 288.2 eV, respectively, while the CC bond peak at 284.2 eV is the most significant. Figure 2 In (c), the B 1s spectrum shows the binding energy of the BN bond, which is 192.5 eV. Figure 2 The N 1s spectrum of (d) shows three obvious peaks at 399.4 eV, 400.1 eV and 401.2 eV, which correspond to the characteristic peaks of pyridine N, pyrrole N and graphite N, respectively. Figure 2 (e) shows the XPS spectrum of O 1s, with peaks of C=O bond, CO bond and BO bond appearing at 530.8 eV, 531.5 eV and 532.5 eV respectively. These characteristic peaks provide important basis for a deeper understanding of the structural characteristics of boron-nitrogen co-doped hollow carbon nanocages.
[0020] Example 1: H3BO3 nanoparticles and PAA solution were accurately weighed in a mass ratio of 1:20, and the two were uniformly mixed by combining ultrasonic treatment and magnetic stirring. Subsequently, the H3BO3 / PAA mixed solution was uniformly coated on a smooth flat substrate using precision coating technology to form a H3BO3 / PAA film of uniform thickness. Next, the film was transferred to a vacuum oven and heat treated at 180°C for 1 hour. This process was intended to promote the curing reaction (i.e., imidization) to convert PAA into PI, and the H3BO3 nanoparticles were successfully embedded in the PI matrix to form an H3BO3 / PI composite film. Laser induction was performed on the H3BO3 / PI composite film using a CO2 laser direct writing device. The laser power was set to 10 watts and the scanning speed was set to 50 mm / s, so that a carbonization reaction occurred in the local area. Under the action of the laser, the boron element in H3BO3 and the nitrogen element in PI were introduced into the carbon structure to form a boron-nitrogen co-doped carbon structure material in situ. The film treated with laser direct writing was carefully placed in deionized water at 60°C for 120 minutes. During this process, the hot water caused the H3BO3 nanoparticles to dissolve and be removed from the carbon structure, leaving boron-nitrogen co-doped hollow carbon nanocages on the film. The film sample that had been treated with template removal was placed in a vacuum drying oven and dried at 80°C for 1 hour to remove residual moisture, and finally a boron-nitrogen co-doped hollow carbon nanocage product was successfully prepared.
[0021] Example 2: H3BO3 nanoparticles and PAA solution were accurately weighed in a mass ratio of 1:30, and the two were uniformly mixed by combining ultrasonic treatment and magnetic stirring. Subsequently, the H3BO3 / PAA mixed solution was uniformly coated on a smooth flat substrate using precision coating technology to form a H3BO3 / PAA film of uniform thickness. Next, the film was transferred to a vacuum oven and heat treated at 200°C for 1 hour. This process was intended to promote the curing reaction (i.e., imidization) to convert PAA into PI, and the H3BO3 nanoparticles were successfully embedded in the PI matrix to form an H3BO3 / PI composite film. Laser induction was performed on the H3BO3 / PI composite film using a CO2 laser direct writing device. The laser power was set to 20 watts and the scanning speed was set to 100 mm / s, so that a carbonization reaction occurred in the local area. Under the action of the laser, the boron element in H3BO3 and the nitrogen element in PI were introduced into the carbon structure to form a boron-nitrogen co-doped carbon structure material in situ. The film treated with laser direct writing was carefully placed in deionized water at a temperature of 80°C and immersed for 90 minutes. In this process, the hot water caused the H3BO3 nanoparticles to dissolve and be removed from the carbon structure, leaving boron-nitrogen co-doped hollow carbon nanocages on the film. The film sample that had been treated with template removal was placed in a vacuum drying oven and dried at a temperature of 80°C for 1 hour to remove residual moisture, and finally the boron-nitrogen co-doped hollow carbon nanocage product was successfully prepared.
[0022] Example 3: H3BO3 nanoparticles and PAA solution were accurately weighed at a mass ratio of 1:40, and the two were uniformly mixed by combining ultrasonic treatment and magnetic stirring. Subsequently, the H3BO3 / PAA mixed solution was uniformly coated on a smooth flat substrate using precision coating technology to form a H3BO3 / PAA film of uniform thickness. Next, the film was transferred to a vacuum oven and heat treated at 180°C for 1 hour. This process was intended to promote the curing reaction (i.e., imidization) to convert PAA into PI, while the H3BO3 nanoparticles were successfully embedded in the PI matrix to form an H3BO3 / PI composite film. Laser induction was performed on the H3BO3 / PI composite film using a CO2 laser direct writing device. The laser power was set to 15 watts and the scanning speed was set to 50 mm / s, so that a carbonization reaction occurred in the local area. Under the action of the laser, the boron element in H3BO3 and the nitrogen element in PI were introduced into the carbon structure to form a boron-nitrogen co-doped carbon structure material in situ. The film treated with laser direct writing was carefully placed in deionized water at a temperature of 100°C and immersed for 60 minutes. In this process, the hot water caused the H3BO3 nanoparticles to dissolve and be removed from the carbon structure, leaving boron-nitrogen co-doped hollow carbon nanocages on the film. The film sample that had been treated with template removal was placed in a vacuum drying oven and dried at a temperature of 80°C for 1 hour to remove residual moisture, and finally the boron-nitrogen co-doped hollow carbon nanocage product was successfully prepared.
[0023] Example 4: H3BO3 nanoparticles and PAA solution were accurately weighed at a mass ratio of 1:50, and the two were uniformly mixed by combining ultrasonic treatment and magnetic stirring. Subsequently, the H3BO3 / PAA mixed solution was uniformly coated on a smooth flat substrate using precision coating technology to form a H3BO3 / PAA film of uniform thickness. Next, the film was transferred to a vacuum oven and heat treated at 200°C for 1 hour. This process was intended to promote the curing reaction (i.e., imidization) to convert PAA into PI, and the H3BO3 nanoparticles were successfully embedded in the PI matrix to form an H3BO3 / PI composite film. Laser induction was performed on the H3BO3 / PI composite film using a CO2 laser direct writing device. The laser power was set to 20 watts and the scanning speed was set to 100 mm / s, so that a carbonization reaction occurred in the local area. Under the action of the laser, the boron element in H3BO3 and the nitrogen element in PI were introduced into the carbon structure to form a boron-nitrogen co-doped carbon structure material in situ. The film treated with laser direct writing was carefully placed in deionized water at a temperature of 80°C and immersed for 90 minutes. In this process, the hot water caused the H3BO3 nanoparticles to dissolve and be removed from the carbon structure, leaving boron-nitrogen co-doped hollow carbon nanocages on the film. The film sample that had been treated with template removal was placed in a vacuum drying oven and dried at a temperature of 80°C for 1 hour to remove residual moisture, and finally the boron-nitrogen co-doped hollow carbon nanocage product was successfully prepared.
[0024] Example 5: H3BO3 nanoparticles and PAA solution were accurately weighed at a mass ratio of 1:60, and the two were uniformly mixed by combining ultrasonic treatment and magnetic stirring. Subsequently, the H3BO3 / PAA mixed solution was uniformly coated on a smooth flat substrate using precision coating technology to form a H3BO3 / PAA film of uniform thickness. Next, the film was transferred to a vacuum oven and heat treated at 180°C for 1 hour. This process was intended to promote the curing reaction (i.e., imidization) to convert PAA into PI, while the H3BO3 nanoparticles were successfully embedded in the PI matrix to form an H3BO3 / PI composite film. Laser induction was performed on the H3BO3 / PI composite film using a CO2 laser direct writing device. The laser power was set to 20 watts and the scanning speed was set to 100 mm / s, so that a carbonization reaction occurred in the local area. Under the action of the laser, the boron element in H3BO3 and the nitrogen element in PI were introduced into the carbon structure to form a boron-nitrogen co-doped carbon structure material in situ. The film treated with laser direct writing was carefully placed in deionized water at a temperature of 100°C and immersed for 60 minutes. In this process, the hot water caused the H3BO3 nanoparticles to dissolve and be removed from the carbon structure, leaving boron-nitrogen co-doped hollow carbon nanocages on the film. The film sample that had been treated with template removal was placed in a vacuum drying oven and dried at a temperature of 80°C for 1 hour to remove residual moisture, and finally the boron-nitrogen co-doped hollow carbon nanocage product was successfully prepared.
[0025] It should be noted that the above content only illustrates the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.
Claims
1. A method for in-situ preparation of boron-nitrogen co-doped hollow carbon nanocages by laser induction, characterized in that: The following steps are involved: (1) Selecting boric acid H3BO3 nanoparticles with uniform particle size as the model boron doping source, and preparing the precursor liquid polyamic acid PAA of polyimide PI as the carbon matrix and nitrogen doping source; (2) uniformly dispersing the boric acid H3BO3 nanoparticles described in step (1) in the PAA solution to form a H3BO3 / PAA mixed solution; (3) coating the mixed solution described in step (2) to prepare a H3BO3 / PAA film, and performing a high-temperature imidization reaction to form a H3BO3 / PI composite film; (4) using laser direct writing technology to perform laser induction on the H3BO3 / PI composite film described in step (3) to in situ form a boron-nitrogen co-doped carbon structure material; (5) Soaking the film described in step (4) in hot deionized water to remove the template and obtain a boron-nitrogen co-doped hollow carbon nanocage structure; (6) Drying the sample after removing the template in step (5) to obtain the final boron-nitrogen co-doped hollow carbon nanocage product.
2. The method for laser-induced in-situ preparation of boron-nitrogen co-doped hollow carbon nano cages according to claim 1, characterized in that: In step (1), the boric acid H3BO3 nanoparticles are used as a hard template for preparing boron-nitrogen co-doped hollow carbon nanocages.
3. The method for laser-induced in-situ preparation of boron-nitrogen co-doped hollow carbon nano cages according to claim 1, characterized in that: In step (2), the mass ratio of boric acid H3BO3 nanoparticles to PAA solution is in the range of 1:20 to 1:
60.
4. The method for laser-induced in-situ preparation of boron-nitrogen co-doped hollow carbon nano cages according to claim 1, characterized in that: The H3BO3 / PAA film prepared by coating in step (3) has a uniform thickness.
5. The method for laser-induced in-situ preparation of boron-nitrogen co-doped hollow carbon nano cages according to claim 1, characterized in that: In step (4), the laser power is 10-20 W and the scanning speed is 50-100 mm / s.
6. The method for laser-induced in-situ preparation of boron-nitrogen co-doped hollow carbon nano cages according to claim 1, characterized in that: In step (5), the temperature of the hot water is 60-100° C., and the soaking time is 60-120 minutes.